Transformationen städtischer Umwelt: Das Beispiel Linz, 1700 bis 1900 - Stöger, Georg (2021)
The book examines long-term transformations of the urban environment during the 18th and 19th centuries by using the example of Linz (Austria). The topics covered range from water, energy and food supply, urban and suburban green spaces to natural impacts such as epidemics, subsistence crises and natural hazards.